Respuesta :

Answer:

The answer is option A

Step-by-step explanation:

The sequence above is an arithmetic sequence

For an nth term in an arithmetic sequence

A(n) = a + ( n - 1)d

where a is the first term

n is the number of terms

d is the common difference

From the question

a = 38

d = 32 - 38 = - 6 or 20 - 26 = - 6

Substitute the values into the above formula

A(n) = 38 + (n - 1)-6

= 38 - 6n + 6

We have the final answer as

A(n) = 44 - 6n

Hope this helps you

Answer:

a

Step-by-step explanation:

you're welcome!